"Sandwich" Diimine‐Copper Catalysts for C−H Functionalization by Carbene Insertion. Issue 31 (10th June 2022) - Klimovica, Kristine; Heidlas, Julius X.; Romero, Irvin; Le, Thanh V.; Daugulis, Olafs
Abstract: We report here "sandwich" diimine‐copper(I) catalysts for C(sp 3 )−H bond functionalization. Reactions of alkanes and ethers with trimethylsilyldiazomethane, ethyl diazoacetate, and trifluoromethyl‐diazomethane have been demonstrated. We also report C(sp 3 )−H bond methylation, benzylation, and diphenylmethylation by diazomethane, aryldiazomethanes, and diphenyldiazomethane. These reactions are rare examples of base‐metal catalyzed, intermolecular C(sp 3 )−H functionalizations by employing unactivated diazo compounds. Electrophilicity and unique steric environment of "sandwich"‐copper catalysts are likely reasons for their catalytic efficiency. Abstract : A new catalyst platform for C(sp 3 )−H bond functionalization has been discovered. "Sandwich" diimine‐copper(I) complexes catalyze reactions of alkane, ether, and amine C−H bonds with a large panel of diazo compounds. Additionally, the first metal‐catalyzed C(sp 3 )−H methylation by CH2 N2 is disclosed. The electrophilicity and extreme steric bulk of these catalysts are likely reasons for their efficiency.